SEROLOGICAL STUDY OF BULGARIAN PATIENTS WITH BRUCELLOSIS - Rumiana Nenova; Iskra Tomova; Liliya Goryanova (Problems of Infectious and Parasitic Diseases, 2021)
Background: Brucellosis is a widespread zoonotic infection with significant health and socio-economic impacts. This determines the need of a reliable laboratory diagnosis both in endemic areas around the world and in countries where it is rare and under diagnosed. Due to prolongedand hazardous cultivation procedures, the diagnosis is mostly serologically confirmed.